MENINGKATKAN HASIL BELAJAR IPS DENGAN METODE INKUIRI PADA SISWA KELAS IX-1 SMP NEGERI 177 JAKARTA SEMESTER 1 TAHUN AJARAN 2016/2017 - Eno Eno (STKIP ROKANIA, 2021)
The purpose of the study was to find out the effectiveness of the inquiry method in improving social studies learning outcomes for developing and developed countries for class XI-1 students of SMP Negeri 177 Jakarta Semester 1 of the 2016/2017 academic year. The research method is classroom action research. Data collection techniques with observation and multiple choice tests. The sample is 35 students in class XI-1 SMP Negeri 177 Jakarta. Data analysis techniques with percentages. The result of the research is that learning with inquiry-based teaching for social studies material in developing and developed countries has a positive impact on improving student achievement which is marked by an increase in student learning mastery in each cycle, namely cycle I (62.50%), cycle II (85.00 %), cycle III (100%).